Genome-Wide Identification and Expression Analysis Elucidates the Potential Role of PFK Gene Family in Drought Stress Tolerance and Sugar Metabolism in Cotton - Mehari, Teame Gereziher; Xu, Yanchao; Umer, Muhammad Jawad; Hui, Fang; Cai, Xiaoyan; Zhou, Zhongli; Hou, Yuqing; Wang, Kai; Wang, Baohua; Liu, Fang (Frontiers in Genetics, 2022)
Drought has been identified as a major threat for global crop production worldwide. Phosphofructokinase (PFK) is vital for sugar metabolism. During phosphorylation, plants have two enzymes: ATP-dependent phosphofructokinase (PFK) and pyrophosphate-dependent fructose-6-phosphate phosphotransferase (PFP). Genome-wide identification led to the identification of 80 PFK genes, 26 genes in G. hirsutum and G. barbadense and 14 genes in G. arboreum and G. raimondii. Phylogenetic, gene structure and motif analyses showed that PFK genes were grouped into two main categories namely PFK and PFP with 18 and 8 genes in the allotetraploid species, whereas 10 PFK and 4 PFP genes in the diploid species respectively. Using the RNA-seq expressions of 26 genes from GhPFK, a co-expression network analysis was performed to identify the hub genes. GhPFK04, GhPFK05, GhPFK09, GhPFK11, GhPFK13, GhPFK14, and GhPFK17 in leaves, whereas GhPFK02, GhPFK09, GhPFK11, GhPFK15, GhPFK16 and GhPFK17 in root tissues were found as hub genes. RT-qPCR analysis validated the expressions of identified hub genes. Interestingly GhPFK11 and GhPFK17 were identified as common hub genes and these might be the true candidate genes involved in the drought stress tolerance. In the KEGG enrichment analysis, amino acids like L-valine, L-histidine, L-glutamine, L-serine, L-homoserine, L-methionine, L-cysteine and gluconic acid were significantly upregulated, whereas sugars mainly fructose-1-phosphate, D-mannitol, D-sorbitol, dulcitol and lactose were significantly downregulated during drought stress. Genome-wide analysis paves the way for a deeper understanding of the PFK genes and establishes the groundwork for future research into PFK's role in enhancing drought stress tolerance and sugar metabolism in cotton.